Analisis Faktor-Faktor Resistensi Individual Pada Perubahan Kepemimpinan di PT Alamjaya Wirasentosa Kota Gunungsitoli - Try Wahyuni Ayu Waruwu; Fatolosa Hulu; Eliagus Telaumbanua; Syah Abadi Mendrofa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
This research analyzes Individual Resistance Factors in leadership Change at PT. Alamjaya Wirasentosa Gunungsitoli City, Individual resistance to change is the resistance that arises in individuals towards changes in an organization, while we know that changes must be made to advance the performance of an organization. Based on observations, there is still an attitude of resistance shown by each employee towards the changes made. The aim of the research is to find out how individual resistance occurs among employees due to leadership changes at PT. Alamjaya Wirasentosa, Gunungsitoli City. In conducting this research, qualitative research methods were used using data collection techniques, namely observation, interviews and documentation. The data analysis technique is data reduction, data presentation and conclusion drawing. The sources of informants for this research were 3 people. The research results show that changes at PT. Alamjaya Wirasentosa Gunungsitoli City occurred when there was a change of leadership, employees felt that with a change of leadership there would certainly be changes that would follow in terms of work methods and rules or existing habits. Individual resistance occurs when fear factors and selective perception exist in the individual himself. Based on the interview results, these two factors are the biggest drivers of individual resistance in employees.